CAPTURE ZONE, TRAVEL TIME, AND SOLUTE-TRANSPORT PREDICTIONS USING INVERSE MODELING AND DIFFERENT GEOLOGICAL MODELS - Harrar W.G.; Sonnenborg T.O.; Henriksen H.J. (My University, 2003)
Six regional-scale flow models are compared to gain insight into how different representations of hydraulic-conductivity distributions affect model calibration and predictions. Deterministic geological models were used to define hydraulic-conductivity distributions in two steady-state flow models that were calibrated to heads and baseflow estimates using inverse techniques. Optimized hydraulic-conductivity estimates from the two models were used to calculate layer and model mean hydraulic-conductivity values. Despite differences in the two geological models, inverse calibration produced mean hydraulic-conductivity values for the entire model domain that are quite similar. The layer and model mean hydraulic-conductivity values were used to generate four additional flow models and forward runs were performed. All of the models adequately simulate the observed heads and total baseflow. The six flow models were used to predict the steady-state impact of a proposed well field, and the flow solutions were used in simulating particle tracking and solute transport. Results of the predictive simulations show that, for this example, simple models of heterogeneity produce capture zones similar to more complex models, but with very different travel times and breakthroughs. Inverse modeling combined with different geological models can provide a measure of capture zone and breakthrough reliability.
Keywords: SEDIMENTARY HETEROGENEITY; GEOLOGICAL MODELS; ZONATION; CAPTURE ZONE; INVERSE MODELING; PREDICTIONS